First report of mites and fleas associated with sigmodontine rodents from Corrientes province, Argentina - Lareschi, Marcela (2006)
Fleas (Insecta: Siphonaptera) and mesostigmate mites (Acari: Laelapidae) are common ectoparasitic associates of sigmodontine rodents in the Neotropics of South America. In Argentina, most of the research on ectoparasitic arthropods has been carried out on rodents from Buenos Aires Province (Autino and Lareschi, 1998; Lareschi and Mauri, 1998), while only a few small studies have been done in other areas of the country, such as the northwest (Lareschi et al., 2003a), and the Monte Desert Biome in Mendoza Province (Lareschi et al., 2004). Unfortunately, very little information is available from the region between the Paraná and Uruguay rivers in northeastern Argentina. From Corrientes Province, only the mite Laelaps manguinhosi Fonseca has been reported parasitizing sigmodontine rodents (Lareschi et al., 2001), and no rodent fleas have been reported in the literature. From non-rodents, the mite Androlalaelaps fahrenholzi (Berlese) has been mentioned associated with the marsupial Thylamys pusilla (Desmarest) (Lareschi and Mauri, 1998), and the flea Rhopalopsyllus lutzi (Baker) with the armadillo Dasypus hybridus (Desmarest) (Autino and Lareschi, 1998). In this paper, we present the first faunal inventory of mites and fleas associated with sigmodontine rodents from Corrientes Province, Argentina.